EUROPE AND THE MEDITERRANEAN: AN AREA OF GROWING INTERDEPENDENCE - Gugan, Daniel (European Scientific Journal, ESJ, 2013)
The aim of this study is to show several areas (societal sectors) of interdependence between the two halves of the Euro-Mediterranean region. The northern half of the region (in its widest geographical sense the EU) and the southern half (Maghreb and Mashreq countries on the southern shore of the Mediterranean Sea) have several common security issues and interests which makes them highly interdependent. After going through the main issue areas of interdependence, the core assumption of the study will be lined out, which argues that Europe and the Mediterranean reached such a high level of security interdependence that they can be treated now as a single security complex.